Linking commuting stress to job satisfaction and turnover intention: The mediating role of burnout. (2nd April 2016) - Amponsah-Tawiah, Kwesi; Annor, Francis; Arthur, Beckham Godfred
ABSTRACT: This study uses structural equation modelling to test a model that posits that commuting stress would have direct and indirect effects (through burnout) on employee job satisfaction and turnover intention. Based on a sample ( N = 336) of employees from diverse occupations in Ghana, the results partly supported the authors' hypothesized model. Commuting stress was positively related to burnout and turnover intention but had no direct relationship with job satisfaction. In addition, commuting stress was indirectly related to job satisfaction and turnover intention via burnout. These results were found to be invariant for men and women. Implications of the findings for theory and practice are discussed.